2013
DOI: 10.1371/journal.pone.0061757
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive, Multi-Scale Dynamical Model of ErbB Receptor Signal Transduction in Human Mammary Epithelial Cells

Abstract: The non-receptor tyrosine kinase Src and receptor tyrosine kinase epidermal growth factor receptor (EGFR/ErbB1) have been established as collaborators in cellular signaling and their combined dysregulation plays key roles in human cancers, including breast cancer. In part due to the complexity of the biochemical network associated with the regulation of these proteins as well as their cellular functions, the role of Src in EGFR regulation remains unclear. Herein we present a new comprehensive, multi-scale dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…5,6 HER2 belongs to human epidermal growth factor receptor (EGFR, HER) family, which includes 4 closely related members, HER1 (EGFR and ErbB1), HER2 (ErbB2), HER3 (ErbB3), and HER4(ErbB4). [7][8][9] HER2 can dimerize with other HER members to play a key role in cell signaling transduction. 9 Gastric cancers at advanced stages express higher levels of HER2 compared to cancers at early stages.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 HER2 belongs to human epidermal growth factor receptor (EGFR, HER) family, which includes 4 closely related members, HER1 (EGFR and ErbB1), HER2 (ErbB2), HER3 (ErbB3), and HER4(ErbB4). [7][8][9] HER2 can dimerize with other HER members to play a key role in cell signaling transduction. 9 Gastric cancers at advanced stages express higher levels of HER2 compared to cancers at early stages.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed that PKC-␦ (61, 62), protein kinase A (61-64), Rho kinase (65), and LIM kinase (66), as well as lipid kinase diacylglyecerol kinase ␦ and phospholipase D modulate EGFR endocytosis (64, 67, 68, 68 -70). Finally, c-Src has been shown to promote EGFR endocytosis likely into a recycling compartment (71)(72)(73)(74). A previous study showed that PMA treatment of ErbB2-transfected fibroblasts induced the juxtamembrane threonine-686 phosphorylation of ErbB2, as well as ErbB2 internalization and intra-cytoplasmic accumulation, but no further characterization of intracellular compartments was carried out (75).…”
mentioning
confidence: 99%
“…With knowledge on the energetics and mechanisms of endocytic pathways emerging, reliable computational models can be developed [86]. However, we must first acquire improved characterization of NPs as the quality of the data input will determine the quality of results that can be extracted from these models.…”
Section: Upcoming Technologies and Testing Platformsmentioning
confidence: 99%